Application of game theory-communication and cooperation - Ang, Ru Ping (2008)
With the exponential growth in information flows globally, the research aims to investigate the level of cooperation under economic game situations among market players. The communication levels have been further segregated into 3 communication forms-no communication, one-way communication and two-way communication.